Translating orality, recreating otherness - Rosa, Alexandra Assis (2017)
This article discusses the problem posed by linguistic variation for interlingual translation, in particular by the relation between language, context and identity in speech and orality, within the framework of Descriptive Translation Studies. It starts by defining linguistic variation as a correlation of linguistic form, communicative meaning and sociocultural value. It examines the particular case of literary representation of varieties to suggest strategies and procedures for their translation. It ends with an analysis of selected examples of canonized British fiction and their translation into European Portuguese, and a discussion of causes and consequences of the patterning resulting from the translation of speech and orality in fiction.